Instilling the Value of Moral Karimah Through Daily Activities in Ra Al-Mardliyyah - Nur Hotimaha; Faridatul Jannah; Fitri Inayah; Dini Zainia Nafi' (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2026)
The cultivation of akhlakul karimah (noble moral values) in early childhood is an essential foundation for shaping Islamic personality and character during the golden age of development. This study aims to describe how the implementation of daily activities at RA Al-Mardliyyah serves as an effective means of instilling akhlakul karimah values in students. The research employed a descriptive qualitative approach using observation, interviews, and documentation techniques involving teachers and children’s learning activities. The results indicate that the cultivation of akhlakul karimah at RA Al-Mardliyyah is carried out through three main strategies. First, daily routine habituation activities, such as praying, greeting others, maintaining cleanliness, and practicing time discipline, which foster values of politeness, responsibility, and discipline. Second, teacher role modeling and an Islamic environment, where teachers act as role models for good behavior and create a religious, caring, and affectionate classroom atmosphere. Third, the integration of moral values into thematic learning, such as the themes “Myself” and “My Environment,” which teach children gratitude, care, and respect for Allah’s creation. In conclusion, daily activities at RA Al-Mardliyyah not only develop positive habits but also serve as a medium for the natural and enjoyable internalization of Islamic values. Through habituation, role modeling, and thematic integration, children are guided to grow into individuals with akhlakul karimah in accordance with the teachings of Islam.